Adiposity is related to decrements in cardiorespiratory fitness in obese and normal‐weight children. Issue 2 (6th May 2015) - Tsiros, M. D.; Coates, A. M.; Howe, P. R. C.; Walkley, J.; Hills, A. P.; Wood, R. E.; Buckley, J. D.
Summary: Background: Obese children are typically less physically active than their normal‐weight peers and are often assumed to be 'unfit'. Objective: Investigate the relationships between adiposity, physical activity levels and cardiorespiratory fitness (CRF) in obese and normal‐weight children. A secondary aim was to examine obese/normal‐weight differences in CRF. Methods: Obese ( N  = 107) and normal‐weight ( N  = 132) 10–13‐year‐olds participated. Fat‐free mass (FFM), percent fat, physical activity and peak oxygen uptake (VO2peak ) were assessed. Analyses were adjusted for socioeconomic status (SES). Results: Higher percent fat was inversely associated with VO2peak normalized for mass ( r  = −0.780, P  < 0.001) even after controlling for physical activity ( r  = −0.673, P  < 0.001). While higher percent fat was also inversely associated with VO2peak normalized for FFM, this was only significant in males ( r  = −0.247, P  = 0.004) and did not persist after controlling for physical activity ( r  = −0.059 P  = 0.526). Compared with normal‐weight children, obese children had higher absolute VO2peak, lower VO2peak corrected for mass ( P  ≤ 0.009) and lower VO2peak corrected for FFM ( P  = 0.041) that did not persist after controlling for SES ( P  = 0.086). Conclusion: Obesity‐related inefficiencies in CRF were evident. Higher adiposity was associated with poorer CRF relative to mass, irrespective of physical activity levels. However, low physical activity levels may be responsible for associations between adiposity and CRF relative to FFM seen in boys, indicating the importance of encouraging physical activity.